Youth crime and youth culture in the inner city - Sanders, Bill, 1972- (Routledge advances in sociology., 2005)
Youth Crime and Youth Culture in the Inner City offers an interpretive account of juvenile delinquency within the modern inner city, an environment which is characterized by a long history of social deprivation and high rates of crime.